Problems of Information Technology-Based Zoning PPDB Implementation at SMAN 3 Banjarmasin - Safitri, Aulia; Muharramah, Nauriatul; Uma, Niksah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
New Student Admission (PPDB) is a school activity that is carried out every year. The current system for junior, vocational, and high schools uses a zoning system. This study aims to determine the implementation of school policies, human resource development, infrastructure, and technical support related to the implementation of IT-based PPDB at SMAN 3 Banjarmasin. This research involved 1 principal, three members of the PPDB committee, three teachers, parents of students, and 4 students at SMAN 3 Banjarmasin. The research aims to implement PPDB zoning based on information technology, namely policies, infrastructure, human resource development, and supporting factors in PPDB. Data collection is carried out by means of observation, interviews, and documentation. After the data is collected, it is processed and analyzed in a qualitative descriptive manner. The results of this study show that in the implementation of IT-based zoning PPDB, there are several problems faced by the PPDB involved in SMAN 3 Banjarmasin, such as student quota restrictions, data manipulation, lack of understanding of prospective students and parents of the PPDB zoning system, network problems, teacher strategies in adjusting learning to the student zoning path, and errors on websites and networks. Based on the findings, it is hoped that the PPDB committee will prepare carefully related to the technical implementation of this PPDB and simulate registration before the official period begins to help users understand the stages.